Skeletal muscle myosin heavy chain fragmentation as a potential marker of protein degradation in response to resistance training and disuse atrophy - Plotkin, D. L.; Mattingly, M. L.; Anglin, D. A.; Michel, J. M.; Godwin, J. S.; McIntosh, M. C.; Kontos, N. J.; Bergamasco, J. G. A.; Scarpelli, M. C.; Angleri, V.; Taylor, L. W.; Willoughby, D. S.; et al. (Experimental Physiology, 2024)
We examined how resistance exercise (RE), cycling exercise and disuse atrophy affect myosin heavy chain (MyHC) protein fragmentation. The 1boutRE study involved younger men (n = 8; 5 ± 2 years of RE experience) performing a lower body RE bout with vastus lateralis (VL) biopsies being obtained prior to and acutely following exercise. With the 10weekRT study, VL biopsies were obtained in 36 younger adults before and 24 h after their first/naïve RE bout. Participants also engaged in 10 weeks of resistance training and donated VL biopsies before and 24 h after their last RE bout. VL biopsies were also examined in an acute cycling study (n = 7) and a study involving 2 weeks of leg immobilization (n = 20). In the 1boutRE study, fragmentation of all MyHC isoforms (MyHCTotal) increased 3 h post-RE (~200%, P = 0.018) and returned to pre-exercise levels by 6 h post-RE. Interestingly, a greater magnitude increase in MyHC type IIa versus I isoform fragmentation occurred 3 h post-RE (8.6 ± 6.3-fold vs. 2.1 ± 0.7-fold, P = 0.018). In 10weekRT participants, the first/naïve and last RE bouts increased MyHCTotal fragmentation 24 h post-RE (+65% and +36%, P < 0.001); however, the last RE bout response was attenuated compared to the first bout (P = 0.045). Although cycling exercise did not alter MyHCTotal fragmentation, ~8% VL atrophy with 2 weeks of leg immobilization increased MyHCTotal fragmentation (~108%, P < 0.001). Mechanistic C2C12 myotube experiments indicated that MyHCTotal fragmentation is likely due to calpain proteases. In summary, RE and disuse atrophy increase MyHC protein fragmentation. Research into how ageing and disease-associated muscle atrophy affect these outcomes is needed.